Double-lumen arterial balloon catheter technique for Onyx embolization of dural arteriovenous fistulas: initial experience. (8th June 2013) - Chiu, Albert Ho Yuen; Aw, Grace; Wenderoth, Jason David
Abstract : Background: Dural arteriovenous fistulas are vascular malformations with variable clinical symptoms that range in severity from completely asymptomatic to seizures, dementia, loss of vision and intracranial hemorrhage. Historically, surgical obliteration was the treatment of choice but, more recently, endovascular embolization has become the first-line treatment. The liquid embolic agent Onyx (ethyl vinyl copolymer) has become the agent of choice, but problems with reflux around the delivery microcatheter and inadvertent venous penetration have arisen. Methods and results: We present six cases in which the double-lumen balloon microcatheter was used to transarterially embolize dural arteriovenous fistulas via injection of Onyx through the wire lumen. Depending on the individual pathology a venous balloon was also used in some cases. The advantages and disadvantages of the use of these devices are discussed. Conclusions: We consider that the use of the double-lumen balloon technique for fistula embolization has the potential for reducing overall procedural times, procedural failures and catheter retention in certain situations. In such cases we would advocate this as a first-line technique. When lower profile, more navigable balloon catheters become available, this may become the standard of care.